Never go back eaudiobook 10 things you'll never do again. - Cloud, Henry (Tantor Media, 2014)
Everyone makes mistakes, big and small. Sometimes our mistakes take us down the wrong path and send us spiraling into destructive life patterns, and sometimes we learn a lesson and never make the same mistake again. But how? How do we recognize our destructive patterns, make new choices, and then follow through? In Never Go Back , bestselling author Dr. Henry Cloud shares ten doorways to success—and once we walk through these new pathways, we never go back again. His proven method—based on grace, not guilt—outlines ten common life patterns that sabotage success and lays out clear, concrete steps you can take to overcome them. You'll see your relationships flourish, your personal life enhanced, and your faith strengthened. Dr. Cloud's powerful message reveals doorways to understanding—once you enter them, you will get from where you were to where you want to be. With a winning combination of eternal principles, spiritual wisdom, and modern scientific data, Never Go Back will put your heart in the right place with yourself and with God.